PENGARUH KOMPOS TKKS DAN ABU BOILER KELAPA SAWIT TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Gita Harbianto; Armaini '; Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this research was to study the interaction of oil palm empty  fruit bunches compost and boiler ash , and to determine  the appropriate dosage combination forthe growth and yield of onion. The research was conducted in experimental garden of Agricalture faculty University of Riau, Pekanbaru. It lasted from December 2014 until March 2015. The research was done in a Completely Randomized Design with two factors and was replicated three times. The first factor is the compost of oil palm empty fruit bunches consist of four levels. That is without  compost of oil palm empty fruit bunches, 0,3 ton/ha, 0,6 ton/ha, 0,9 ton/ha and 1,2 ton/ha. The second factor is the boiler ash consist of three levels, that is 50 kg/ha, 100 kg/ha and 150 kg/ha.Data analyzedby ANOVAandfurthertestedusing byDuncan`sNewMultiple RangeTest(DNMRT) atthe level of 5%. The result showed the application of combination oil palm empty bunch compost with boiler ash increased the plant hight,number of tubers, diameter of tubers, weight shelf tuber and fresh weight of onion's tuber. The application oil palm empty bunch compost 0,6-1,2 ton/ha not allowed with application of boiler ash, and on the application of boiler ash 50-1,2 kg/ha without application of oil palm empty bunch compot  has showed the highest yield, while the appication of oil palm empty bunch compost 0,3-1,2 ton/ha with boiler ash 50-150 kg/ha also showed the best yield.   Keywords :Onion, Compost Of Oil Palm Empty Fruit Bunches, Boiler Ash